Pengujian Alat Pembangkit Listrik Tenaga Surya Solar Cell Sederhana - Sibuk Ginting; Jusuf Halawa; Libianko Sianturi; Richard A M Napitupulu (Program Studi Teknik Mesin, Universitas HKBP Nommensen, Medan, 2019)
One of the sources of electricity technology is solar cell. in principle solar cell converts solar energy into electrical energy, here a simple solar cell made of copper that is designed simply with copper material containing oxide is made into the negative side of the solar cell and positive as a copper palat which does not contain oxide / is not baked on electric stove in the design of this simple solar cell where the copper cross section area containing oxide with a size of 25cm x 30cm and the size of copper plate that does not contain oxide with U-shaped is 29cm x 32cm and coated with glass as a reflector with a size of 32cm x 34cm where in solar design This simple cell was conducted for 2 days during a solar cell experiment for 2 days with the highest voltage of 4.4 V, which is on the first day and the voltage on the second day gets the highest voltage of 4.0 V with the intensity different light.